Emotion Regulation in Adolescents in the Digital Era in the Context of Social Media and Mental Health: A Systematic Review - Lia, Fitrah Amaliah; Iswinarti (Causalita, 2025)
Emotion regulation is the ability to manage, direct, and adapt emotional responses to various situations. Among adolescents in the digital era, this ability is increasingly vital due to high exposure to social media. This study aims to systematically review the literature on the role of emotion regulation in adolescents, focusing on social media use and its mental health implications. By analyzing peer-reviewed articles from databases such as PubMed, ScienceDirect, and Google Scholar, the findings indicate that poor emotion regulation increases the risk of depression, anxiety, and low self-esteem, particularly due to social comparison and cyberbullying. On the other hand, adaptive emotion regulation acts as a buffer against digital stress. The findings highlight the importance of emotional education and family involvement in promoting digital emotional resilience in adolescents.